(3GdeMGceGJ Hjf TQMi GdETGQGJs - (3GdbWH GdJMJGfj , eMeO (B( (3eMehO (B) (3Hf eMeO GdQGRj, CHh YHO Gddg, bWH GdOjf CHh YHO Gddg GdJMJGfj,J (B766 (3g` s
(3ChdgG (B:s
(3JHOC HGdMhGS GdXGgQI hGdHGWfI JfHg dYdhe HOjgjI hGSJYO dGOQGc GdYdhe GdcSHjI hgh GdeQJHI GdKGfjI hJSei YbdkG HGdedcI s
(3BNQgG (B:s
(3gPG eG JdNU dOjfG ai TQM GdTQM HGdGacGQ GdeJhGdjI Je HYhf Gddg hMSf JhajbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B95s
Keywords: (3GdadSaI hGdefWbs